A liberális gazdaságszervezés alternatívái Közép-Európában a két világháború között - Zachar, Péter Krisztián (Közép-Európai Közlemények, 2013)
The author is dealing in his essay with the topic of the social-economic state-organisation between the two world wars in Central Europe. He is searching for answers to the questions of the root of anti-liberal economic views, therefore he summarizes the feelings of economic theoricians about the economic-social crises after the First World War, which was worsened by the Great Depression of 1929. As a result new economic approaches emerged, criticising the liberal methods and social results of the “Manchester capitalism”. The author explains on the one hand the left-wing theories of „state-capitalism” and „organised capitalism”. On the other hand he deals primarily with the background and ideas of the conservative, catholic thoughts of anti-libertarian, anti-etatist vocational order. The basis for this theory is the catholic social doctrine, an „ethical approach” to economics, which takes its origins in the papal encyclicals Rerum novarum (1891) and Quadragesimo anno (1931). The main thoughts are solidarity and subsidiarity, which lead to an interest representing organizational form where labour unions and capitalist groups can decide together about the economic politics of the “modern welfare state”. This trend did not cease to exist even after the Second World War: the social market economy based on concordance and cooperation between social actors instead of class battle is a descendant of this view in many respects.